The Role of Trading Halts in Monitoring a Specialist Market - Edelen, R. (Review of Financial Studies, 2003)
Journal Article The Role of Trading Halts in Monitoring a Specialist Market Get access Roger Edelen, Roger Edelen University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar Simon Gervais Simon Gervais University of Pennsylvania Address correspondence to Simon Gervais, Finance Department, Wharton School, University of Pennsylvania, Steinberg Hall-Dietrich Hall, Suite 2300, Philadelphia, PA 19104-6367, or e-mail: gervais@wharton.upenn.edu. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 16, Issue 1, January 2003, Pages 263–300, https://doi.org/10.1093/rfs/16.1.0263 Published: 16 June 2015